2021
DOI: 10.1007/s11136-021-02807-3
|View full text |Cite
|
Sign up to set email alerts
|

Association among multimorbidity, physical disability and depression trajectories: a study of urban–rural differences in China

Abstract: Purpose The purpose of this study was to analyse the trajectories of depression in urban and rural areas, and to analyse the relationship among multimorbidity, disability and other variables and trajectories. Methods Data from the China Health and Retirement Longitudinal Study were used. A latent class growth model was used to characterise the trajectories of urban and rural depression symptoms. Chi-square test was used to test the differences in responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…Results from a longitudinal study have confirmed that multimorbidity increases the risk of mental health disorders among older individuals compared to those without a chronic disease ( Yan et al, 2021 ). Multiple linear regression analysis also showed that multimorbidity was positively associated with depression, anxiety, and stress symptoms in the current study.…”
Section: Discussionmentioning
confidence: 89%
“…Results from a longitudinal study have confirmed that multimorbidity increases the risk of mental health disorders among older individuals compared to those without a chronic disease ( Yan et al, 2021 ). Multiple linear regression analysis also showed that multimorbidity was positively associated with depression, anxiety, and stress symptoms in the current study.…”
Section: Discussionmentioning
confidence: 89%
“…There are many family tragedies in the vast rural areas of China, particularly, in the economically underdeveloped regions, where older adults commit suicide, indicating the poor situation of older adults in rural areas (16). In 2018, the per capita disposable income of urban residents in China was CNY 39,251, and that of rural residents was CNY 14,617, which is a large gap (17). In addition, another study has documented the trends and gaps in health disparities between urban and rural areas (18).…”
Section: Introductionmentioning
confidence: 99%
“…While urban residents showed better medication use (44)(45)(46), they were less likely to avoid tobacco and alcohol use. We attribute these differences to China's household registration system that was formally established in 1958, that is, the urban-rural segmentation has led to unfair distributions of resources (e.g., healthcare and cultural or educational resources) and different social relationships as well (4,5). While urban residents may benefit from better access to social welfare, healthcare, institutional social support, and medical information (4,47), rural residents benefit more from stronger social cohesion and close acquaintance networks.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced disparity may also be the result of effective welfare policy (e.g., the communitybased hypertension management service of China's Equalization of Basic Public Health Services policy in 2009, new urbanization in 2014, and the rural revitalization strategy in 2017). Urban areas today have more voluntary or informal organizations than ever before to increase residents' participation in positive and beneficial social activities (5), including volunteering, to better connect with their community (2). Consequently, Chinese middle-aged and older urban residents tend to have more diverse and higher rates of social engagements than their rural counterparts (6); the influence of this resource to help patients adhere to self-monitoring, physical activity, and alcohol avoidance works in a similar fashion to the influence of close kinship and acquaintance networks in rural areas (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation